Timing of hCG administration does not affect pregnancy rates in couples undergoing intrauterine insemination using clomiphene citrate. - Robb, Paul A. (National Medical Association, 2004)
BACKGROUND: Therapeutic intrauterine insemination (IUI) combined with clomiphene citrate ovarian stimulation is widely used to improve pregnancy rates for a variety of disorders. The goal of this study was to elucidate whether hCG administration at 24 or 36 hours after clomiphene citrate stimulation impacts pregnancy rates. METHODS: The study was conducted as a retrospective chart review of 182 clomiphene citrate/IUI cycles in 90 women at the Center for Reproductive Health at the University of Cincinnati Medical Center. Comparisons were made between IUls performed at 24 hours versus 36 hours after hCG. Clinical variables included age of the female partner, semen concentration and motility, and infertility diagnosis. Outcomes were pregnancy rates and live birth rates. Data analysis was performed using Chi square for proportions and Student's t-test for continuous variables. RESULTS: The pregnancy rate was 7% in the 24-hour group and 15.9% in the 36-hour group (P=0.057). However, the live birth rate was 4.0% in the 24-hour group and 8.5% in the 36-hour group (P=0.2). CONCLUSIONS: There is no significant difference in pregnancy rates in couples utilizing clomiphene citrate and undergoing IUI, whether hCG is administered at 24 hours or 36 hours prior to the procedure.